Diagnóstico de la salud y seguridad del trabajo en la Asociación de Emprendedores Agropecuarios “Cuturivi Chico” del cantón Pujilí, provincia de Cotopaxi, 2021-2022. - Flores Tello, Ana Gabriela (2022)
The research was carried out in the association of agricultural entrepreneurs Cuturivi Chico located in the province of Pujilí, Cotopaxi canton, where the members of the association were characterized through socioeconomic indicators and work risk, the objective of this research was to determine the productive activities of the members of the association and know the risks they are exposed to in the same during their daily workdays, in addition to knowing how the pandemic of Covid 19 exceeded in the families of the associates; For which a survey with two blocks of questions was applied, in the first block the members of the association were characterized and in the second block it helped us to determine the daily risks to which they are exposed, having the following results: Where the majority of members are Women and are in an average age of 41-50 years, engaged in agriculture, livestock and trade. 87% of the members of the association are regularly exposed to physical risk factors such as: heat, cold, sunlight, 100% are exposed to biological factors, such as: mosquito bites, more than 83% had accidents and affections in their workplace, such as: cuts, falls, blows, etc., this has brought them musculoskeletal consequences. The indicators on the COVID-19 pandemic virus that we are currently experiencing, the level of exposure to this indicator is 8.7% which is at a low risk of contagion, however, most of the infections were caused by activities outside the farmers, whose purpose is to protect the health of workers and meet the contingencies arising from the conditions of the work, leading them to have a knowledge of what is an occupational hazard and thus prevent accidents at work.